Evaporated mongo milk - Fernandez, Elizabeth M.; Malazo, Rufina G.; Montero, Josefino C. (Diliman, Quezon City College of Engineering, 1976)
This plant which is designed to produce milk from mango beans will have a capacity of 47,000 metric tons a year or 118,000,000 of 14 oz. cans a year. It is to operate 24 hours a day for 300 days a year, requiring a fixed-capital investment of P 8,907,290. With a unit cost of P 0.75 per 14 oz. can of milk and an added income from animal feeds of P 0.78 per kilogram, total annual sales will amount to P 92,904,652. The pay-out time is 1.84 years making this plant economically feasible.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Food processing plants; Milk plants; Mung bean